Poems of Heaven and Hell from Ancient Mesopotamia. Translated and Introduced by N. K. Sandars - Anonymus, A. (1971)
Enūma eliš; description of underworld = Ebeling, Or 18 285; Inanna’s Descent; Adapa; Prayer to Gods of the Night.